Cytoplasmic 3' poly(A) addition induces 5' cap ribose methylation: implications for translational control of maternal mRNA. - Kuge, H (1995)
During the early development of many animal species, the expression of new genetic information is governed by selective translation of stored maternal mRNAs. In many cases, this translational activation requires cytoplasmic poly(A) elongation. However, how this modification at the 3' end of an mRNA stimulates translation from the 5' end is unknown. Here we show that cytoplasmic polyadenylation stimulates cap ribose methylation during progesterone-induced oocyte maturation in Xenopus laevis. Translational recruitment of a chimeric reporter mRNA that is controlled by cytoplasmic polyadenylation coincides temporally with cap ribose methylation during this period. In addition, the inhibition of cap ribose methylation by S-isobutyladenosine significantly reduces translational activation of a reporter mRNA without affecting the increase of general protein synthesis or polyadenylation during maturation. These results provide evidence for a functional interaction between the termini of an mRNA molecule and suggest that 2'-O-ribose cap methylation mediates the translational recruitment of maternal mRNA.